2019
DOI: 10.1167/iovs.18-25721
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine Expression in Murine RPE/Choroid in Response to Systemic Viral Infection and Elevated Levels of Circulating Interferon-γ

Abstract: PURPOSE. To examine how circulating immune mediators in vivo may affect gene and protein expression at the RPE/choroid interface. METHODS. Young mice were systemically infected with lymphocytic choriomeningitis virus (LCMV) or continuously infused with IFN-c. RPE/choroid was isolated and analyzed with whole-transcriptome gene expression microarrays. Selected gene expression findings were validated at the protein level. RESULTS. Both the systemic immune activation from virus infection and the sterile systemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 55 publications
3
11
0
Order By: Relevance
“…Our data support the hypothesis that systemic inflammation may contribute to the development of AMD [25,26], as our basal (corresponding to the side of the choroid) pro-inflammatory stimuli induce pro-inflammatory cytokine release in the RPE and a disruption of the RPE barrier function. These results are also supported by a recent in vivo study that showed that a systemic virus infection can alter the expression of chemokines and complement factors in the RPE/choroid [68].…”
Section: Discussionsupporting
confidence: 76%
“…Our data support the hypothesis that systemic inflammation may contribute to the development of AMD [25,26], as our basal (corresponding to the side of the choroid) pro-inflammatory stimuli induce pro-inflammatory cytokine release in the RPE and a disruption of the RPE barrier function. These results are also supported by a recent in vivo study that showed that a systemic virus infection can alter the expression of chemokines and complement factors in the RPE/choroid [68].…”
Section: Discussionsupporting
confidence: 76%
“…The cells producing the cytokines remain to be specified. RPE in vivo may produce CCL5 and other cytokines in culture for instance in response to viral infection ( 53 ). Given that we studied dissected retina samples from which the RPE and posterior eyecup was removed, it is however likely that retinal cells not RPE or choroidal cells generate these transcripts.…”
Section: Discussionmentioning
confidence: 99%
“…The RPE forms the outer blood-retinal barrier where adhesion and communication between RPE cells is essential to prevent the passage of molecules and ions, and maintain cell polarity. These events allow the correct functioning of the retina and maintain retinal immune privilege [6,7]. Most researchers agree that one of the early events in DR is the dysfunction of RPE, affecting the retina [8].…”
Section: Retinal Pigment Epithelium and Diabetic Retinopathymentioning
confidence: 99%